2021
DOI: 10.3390/en14030643
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Thermal Comfort and Indoor Air Quality Using Real-Time Multiple Environmental Monitoring Data for a Childcare Center

Abstract: Thermal comfort, indoor air quality (IAQ), and energy use are closely related, even though these have different aspects with respect to building performance. We analyzed thermal comfort and IAQ using real-time multiple environmental data, which include indoor air temperature, relative humidity, carbon dioxide (CO2), and particulate matter (e.g., PM10 and PM2.5), as well as electricity use from an energy recovery ventilation (ERV) system for a childcare center. Thermal comfort frequency and time-series analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Continents and countries with evidenced exceedance in the concentrations of CO 2 above the regulatory limits set by both local and international bodies include Asia, North America and Europe. In Asia, South Korea indoor CO 2 levels of range; 381–3623 ppm, 895–2257 ppm, 555.00–1675.00 ppm and 502.7–1261.40 ppm by Kim et al ( 2021 ), Oh and Song ( 2021 ), Yang et al ( 2009 ) and Hwang et al ( 2017 ) in some of the day-care centres and kindergartens exceeded the Korean IAQ recommended levels of 1000 ppm. Also, Malaysia with highest CO 2 levels of 1005.9 ppm (Kamaruzzaman and Razak 2011 ) exceeded the Malaysia Department of Safety and Health set limit of 1000 ppm given by the American Society for Heating, Refrigerating and Air Conditioning Engineers (ASHRAE).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Continents and countries with evidenced exceedance in the concentrations of CO 2 above the regulatory limits set by both local and international bodies include Asia, North America and Europe. In Asia, South Korea indoor CO 2 levels of range; 381–3623 ppm, 895–2257 ppm, 555.00–1675.00 ppm and 502.7–1261.40 ppm by Kim et al ( 2021 ), Oh and Song ( 2021 ), Yang et al ( 2009 ) and Hwang et al ( 2017 ) in some of the day-care centres and kindergartens exceeded the Korean IAQ recommended levels of 1000 ppm. Also, Malaysia with highest CO 2 levels of 1005.9 ppm (Kamaruzzaman and Razak 2011 ) exceeded the Malaysia Department of Safety and Health set limit of 1000 ppm given by the American Society for Heating, Refrigerating and Air Conditioning Engineers (ASHRAE).…”
Section: Resultsmentioning
confidence: 79%
“… Zuraimi and Tham ( 2008 ) Asia (South Korea) PM 10 , PM 2.5 and CO 2 5 years A real-time multiple monitoring sensor 1 childcare centre The operation of energy recovery ventilation (ERV) system showed that the highest CO 2 (2257 ppm) and PM 10 (52.8 μg/m 3 ) levels were reduced by 51.4% and 29.5%, respectively, during the occupied hours. Oh and Song ( 2021 ) Asia (South Korea) PM 10 0–5 years Real-time monitor (Air Guard K) 87 preschools Annual indoor PM 10 level was between 20.9 and 147.5 μg/m 3 in DCCs and 18.7–39.7 μg/m 3 in the kindergartens’ schools. The indoor PM 10 level in DCCs was the highest.…”
Section: Resultsmentioning
confidence: 99%
“…According to the statistics of relevant departments, the accumulation of household garbage in China is also very serious. Therefore, it can be concluded that the severe urban environment pollution in China has begun to affect people's daily life and environment pollution even has seriously harmed people's health in some places [ 7 , 8 ]. In view of the current situation of urban environment pollution, combined with the impact of environment pollution on people's physical and mental health, as well as China's determination to solve the problem of environment pollution and the immaturity of environment monitoring technology and many other factors, it is very necessary to establish the residential environment pollution monitoring and alarm system.…”
Section: Introductionmentioning
confidence: 99%
“…With the expansion of wireless communication, data storage, small electronic devices, etc., will be able to transfer bigger data for increasing the building performance [19].…”
Section: Methods For Measurements Of the Operative Temperaturementioning
confidence: 99%